Role of Alveolar-Arterial Difference in Estimation of Extravascular Lung Water in COVID-19-Related ARDS - Kutej, Martin; Sagan, Jiri; Ekrtova, Tereza; Strakova, Hana; Buzga, Marek; Burda, Michal; Maca, Jan (Respiratory care, 2024)
BACKGROUND: The dominant feature of COVID-19-associated ARDS is gas exchange impairment. Extravascular lung water index is a surrogate for lung edema and reflects the level of alveolocapillary disruption. The primary aim was the prediction of extravascular lung water index by the alveolar-arterial oxygen difference. The secondary aims were in determining the relationship between the extravascular lung water index and other oxygenation parameters, the [Formula: see text], end-tidal oxygen concentration, pulmonary oxygen gradient ([Formula: see text] minus end-tidal oxygen concentration), and [Formula: see text]. METHODS: This observational prospective single-center study was performed at the Department of Anaesthesiology and Intensive Care, The University Hospital in Ostrava, The Czech Republic, during the COVID-19 pandemic, from March 20, 2020, until May 24, 2021. RESULTS: The relationship between the extravascular lung water index and alveolar-arterial oxygen difference showed only a mild-to-moderate correlation (r = 0.33, P < .001). Other extravascular lung water index correlations were as follows: [Formula: see text] (r = 0.33, P < .001), end-tidal oxygen concentration (r = 0.26, P = .0032), [Formula: see text] minus end-tidal oxygen concentration (r = 0.15, P = .0624), and [Formula: see text] (r = -0.15, P = .01). CONCLUSIONS: The alveolar-arterial oxygen difference does not reliably correlate with the extravascular lung water index and the degree of lung edema in COVID-19-associated ARDS.
Keywords: dospělí; plicní alveoly; Female; Pulmonary Gas Exchange; výměna plynů v plicích; syndrom dechové tísně; Adult; ženské pohlaví; plicní edém; Pulmonary Alveoli; lidé; COVID-19; Pulmonary Edema; Extravascular Lung Water; prospektivní studie; Male; Aged; extravaskulární plicní voda; Oxygen; Prospective Studies; Czech Republic; Respiratory Distress Syndrome; Česká republika; lidé středního věku; senioři; mužské pohlaví; Middle Aged; kyslík; Humans